1980
DOI: 10.1016/0005-2736(80)90408-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by lead of human erythrocyte (Na+ + K+)-adenosine triphosphatase associated with binding of 210Pb to membrane fragments

Abstract: Fragmented human erythrocyte membranes were exposed to PbC12 for 10-40 min at 23°C prior to (Na÷+ K+)-ATPase assay. Inhibition increased with exposure time. Enzyme activity in 5 pg membrane protein was inhibited 50% after a 10-min exposure to 1.0 nmol PbC12 (25 pM final concentration) and was inhibited 100% after 40 rain. When membranes at various concentrations were exposed to PbC12 for 40 min, inhibition was linear with the ratio of PbC12 to protein. Inhibition of 100% was obtained at 0.2 nmol PbC12/pg prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…We found a 50% inhibition of renal Na-K-ATPase at a con centration o f 7 x 10 5M, which is similar to that described for human kidney Na-K-ATPase [48]. Pb causes a very slowly reversible inhibition of the enzyme [31] which is reduced when the concentration of ATP is increased [48], i.e. a competitive inhibition with regard to its substrate as found in the present study.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We found a 50% inhibition of renal Na-K-ATPase at a con centration o f 7 x 10 5M, which is similar to that described for human kidney Na-K-ATPase [48]. Pb causes a very slowly reversible inhibition of the enzyme [31] which is reduced when the concentration of ATP is increased [48], i.e. a competitive inhibition with regard to its substrate as found in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…Many of the trace metals investigated in the present study accumulate pre ferentially in the kidney cortex, e.g., Cd [17], Cu [18], Hg [19], Ni [20], Pb [21], Ur [22,23], and may thereby cause metabolic a n d /o r morphological alterations at structures located within this region of the kidney. They may cause damage to mitochondria, e.g., Cd [17], Cu [24][25][26], Hg [19], Pb [27], Zn [28], or accumulate in ATPase-rich microsomes, e.g., Zn [29], Cu [30], Pb [31], and in the cyto-plasma, e.g. Ni [20], Pb [21], Zn [29], of the proximal tubular epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…PbC1 2 inhibits the phosphatase activity of the human erythrocyte Na + ,K+-ATPase (Caspers and Siegel, 1980), as well as that of rat brain (Siegel et al, 1977). This metal ion can inhibit [ 3H]ouabain binding to the high affinity forms of the cerebromicrovascular Na + ,K+ -ATPase (Caspers et al, 1990) in the same concentration range as that found in the cerebral endothelium during experimental lead intoxication (Toews et al, 1978).…”
Section: Metal Ions and The Na K -Atpasementioning
confidence: 89%
“…The drop in erythrocyte magnesium from the 42nd day on may be explained by a change in the activity of mem brane adenosine triphosphatases (ATPases): Na+-K+-ATPase and Mg2+-ATPase [36], In effect, Torkhovskaya et al [37] have recently demonstrated that an atherogenic diet in rab bits results in decreased activity of erythro cyte membrane Na+-K+-ATPase. Moreover, Caspers and Siegel [38], in a study of the effect of lead in vitro on fragmented human erythrocyte membranes, have indicated that lead acts as an irreversible or very slowly reversible inhibitor of Na+-K+-ATPase and Mg2+-ATPase activities.…”
Section: Discussionmentioning
confidence: 99%